MHD free convection flow of power-law nanofluid film along an inclined surface with viscous dissipation and joule heating. (20th March 2019) - B., Vasu
Abstract : Purpose: The purpose of this study is to present the magnetohydrodynamic (MHD) flow and heat transfer in an accelerating film of a non-Newtonian pseudo-plastic nanofluid along an inclined surface with viscous dissipation and Joule heating. Design/methodology/approach: An incompressible and inelastic fluid is assumed to obey the Ostwald-de-Waele power law model and the action of viscous stresses is conﬁned to the developing momentum boundary layer adjacent to the solid surface. Viscous dissipation and Joule heating on the flow of electrically conducting film in the presence of uniform transverse magnetic field is considered for the Carboxyl Methyl Cellulose (CMC) water-based nanofluid. The fluid is the CMC-water-based with concentration (0.1-0.4 per cent) containing three types of nano-solid particles Cu, Al2 O3 and TiO2 . The modeled boundary layer conservation equations are transformed to dimensionless, coupled and highly non-linear system of differential equations, and then solved numerically by means of a local non-similarity approach with shooting technique. To validate the numerical results, a comparison of the present results is made with the earlier published results and is found to be in good agreement. Findings: The effects of magnetic parameter, Prandtl number, Eckert number and Biot numbers on the velocity and temperature fields are presented graphically and discussed for various values of thermo-physical parameters. It has been found that magnetic field decelerates the fluid velocity for both cases of Newtonian nanofluid and pseudo-plastic nanofluid because of the generated drag-like Lorentz force. This is of great benefit in magnetic materials processing operations, utilizing static transverse uniform magnetic field, as it allows a strong regulation of the flow field. Research limitations/implications: The numerical study is valid for two-dimensional, steady, laminar film flow of Ostwald-de-Waele power law non-Newtonian nanofluid along an inclined plate. A uniform transverse magnetic field of strength B0 is applied perpendicular to the wall. Assume that the base fluid and the nano-solid particles are in thermal equilibrium with no slip effects. The interaction of magnetic field with nanofluid has several potential implications and may be used to deal with the problems such as cooling nuclear reactors by liquid sodium and inducting the flow meter which depends on the potential difference in the fluid along the direction perpendicular to the motion and to the magnetic field. Practical implications: The study has significant applications in magnetic field control of materials processing systems. Originality/value: The results of the present study may be attentiveness to the engineers and applied mathematicians who are interested in hydrodynamics and heat transfer enhancement associated with film flows.